Electrodeposition of Metals and Preparation of Metal Nanoparticles in Nonaqueous Electrolytes and Their Application to Energy Devices - Kazuki YOSHII (The Electrochemical Society of Japan, 2021)
Nonaqueous electrolytes are used in various electrochemical devices as their electrochemical potential window is wider than that of aqueous electrolytes. Electrochemical reactions significantly change depending on the combination of nonaqueous solvent and salt and the dissolved state of the metal ions or redox species in the solvent. Room-temperature ionic liquids (RTILs), a type of nonaqueous solvent, have unique physicochemical properties such as negligible vapor pressure and non-flammability. Their application as reaction media for a variety of reactions, including electrochemical reactions has attracted significant interest, as they enable reactions that cannot proceed in water or organic solvents. We have been researching materials synthesis and energy devices using RTILs and organic electrolytes. Herein, we comprehensively review our research on the electrodeposition of metals, preparation of metal nanoparticles, and secondary batteries using nonaqueous electrolytes.